Heterogeneidade em popula????es de exossomas s??ricos em fun????o de diferentes t??cnicas de purifica????o - Jojoa, Dianny Elizabeth Jimenez (2017)
The physiological and pathological processes are leaded by infinity of mechanisms and metabolic pathways. In the last decades, researches have focused on to small vesicles, the exosomes, from endosomal origin that could be involved in these processes. These vesicles can be released by different cell types carrying important components that could become biomarkers for the diagnosis of diseases or as moldable tools for controlled release of bioactive substances for clinical and therapeutic application. However, one of the challenges in the study of these interesting and versatile microvesicles is the purification process. Currently, significant difficulties are found as the lack of purity, yield and reproducibility revealed in the unreliable data at both the protein and transcriptional levels. Therefore, our aim in the present study was to compare in human serum samples the currently used purification techniques: ExoQuick??? (Systems Biosciences), Total Exosome Isolation (Life Technologies), Ultrafiltration and Ultracentrifugation and Size Exclusion Chromatography as regards to yield, size and purity evaluating, in addition, the reproducibility. The results obtained revealed the existence of differences between the techniques in the amount of particle recovery with sizes corresponding to the exosomes. Ultrafiltration was the most efficient technique followed by polymer precipitation methods and Ultracentrifugation. Protein content diversified considerably, with the Ultrafiltration almost ten times more than Ultracentrifugation. Different profiles of proteins in acrylamide gel were found, with 50 kDa to 70 kDa bands suggesting the co-precipitation of abundant contaminating proteins as albumin. When the chromatography was used to evaluate the recovery efficiency of the other techniques, the result showed no interference in the separation of populations by size, but could represent an additional tool for techniques as Ultrafiltration in the isolation of albumin as the main interfering in the serum samples. Important data were found when particle number normalization was performed in the analysis by the TRPS method, where a reduction of the aggregation and a change in the particle distribution were visible. In our results it was possible to confirm the need for the new reproducible and reliable protocols that can allow the isolation of exosomes for clinical application. On the other hand, our data provide guidance on the use of current methods for obtaining exosomes from serum and other biological fluids.